Role of yeast HAP4 gene in mitochondrial function, oxidative phosphorylation, and apoptosis in response to dna damage - Bui, Van Ngoc; Nguyen, Duong Huy (Academia Journal of Biology, 2025)
Apoptosis plays a crucial role in the normal development and differentiation of multicellular organisms and is essential for embryogenesis, metamorphosis, and elimination of unwanted cells. Like mammalian cells, yeast cells have evolved a number of cellular surveillance mechanisms including DNA damage checkpoint, stimulation of DNA repair, tolerance of DNA damage, and initiation of apoptosis. In Saccharomyces cerevisiae, the HAP4 gene encodes the Hap4 protein which is a subunit of the heme-activated, glucose-repressed Hap2p/3p/4p/5p complex. This complex plays a crucial role in controlling the TCA cycle, the mitochondrial electron transport chain, ATP production and mitochondria biogenesis. Thus, the purpose of this study is to investigate the role of the HAP4 gene by using the BY4742 (wild type) and specific knock-out yeast strains (∆hap4) to elucidate the role of this gene in mitochondrial function and respiration, ATP synthesis, and apoptosis in response to DNA damage triggered by methyl methanesulfonate (MMS) treatment. The findings suggested that the fully functional mitochondria enhanced oxygen consumption and mitochondrial activity, attenuated ROS accumulation, and enabled efficient electron transport and ATP synthesis. High mitochondrial activity is performed as a cellular protective mechanism against oxidative stress. In contrast, deletion of the HAP4 gene (∆hap4), the main regulatory gene for the expression of respiratory proteins, caused a block of the electron transport chain, persistent inhibition of mitochondrial activity, thereby leading to a reduction of oxygen consumption. Low mitochondrial activity resulted in the development of oxidative stress, enhancement of sensitivity to DNA damaging agents. High intracellular ROS levels in ∆hap4 cells posed a significant threat to mitochondrial DNA damage, impairment of mitochondrial respiration, inhibition of glycolytic enzymes (GAPDH, PYK), repression of ATP synthesis, and subsequent induction of cell death (apoptosis).